Genotoksičnost pesticidov, vključenih v spremljanje stanja pitne vode v Sloveniji - Fatur, Tanja (Zdravstveno varstvo, 2006)
Pesticides used to supress plant disease and control pest may affect human health. One of the adverse health affects of pesticides is their genotoxic activity, which leads to permanent changes in deoxyribonucleic acid (DNA), i.e. the so-called mutations. Mutations formed in somatic cells may result in cancer, and those in germ cells can be transmitted to the offspring. They can trigger processess involved in the development of genetically transmitted disease or may cause abortion. The genotoxic potential of pesticides is evaluated by a battery of assays. Drinking water in Slovenia is monitored for the presence of 55 pesticides. The results hitherto obtained for 23 pesticidesshowed no genotoxic potential. Genotoxicity is also assessed for some pesticide metabolites, formed in organisms or in the environment. Very little is known, however, about genotoxicity of pesticides used for a long time, as well as about their metabolites, possible interaction between DNA andmultiple pesticides or pesticides and other chemicals in drinking water. Inview of the yet unclear and unpredictable processes occurring in the organism and the environment, it is crucial to protect human health by keeping concentrations of pesticides in drinking water as low as possible.
Keywords: DNK; genotoksičnost; mutageni; pesticidi; pitna voda; škodljivost